Crayons and IPads: Learning and Teaching of Young Children in the Digital World - Harwood, Debra (SAGE swifts, 2017)
A timely addition to the SAGE Swift Series, Crayons and iPads examines the use of digital technology in the early stages of child development and the way in which learning techniques have evolved in classrooms across the world. Taking the position that tablets provide an accessible learning and instructional tool, Debra Harwood explores how tablets can be used to provoke, ignite, and excite children’s interest in the world around them, arguing that it is through this engagement with technology that new discoveries are made and learning takes place. Guiding readers through research-based insights into children’s thinking, interactions and being, Crayons and iPads offers an important starting point upon which to build play and inquiry-based learning opportunities within early learning programs.